Enhanced cooling rates in laser directed energy deposition with interlayer peening - Mithal, Abeer (2023)
Purpose: This study aims to investigate the effect of mechanical peening on the cooling rate of a subsequently deposited layer in a hybrid additive manufacturing (AM) process. Design/methodology/approach: In this experimental study, 20 layers of 316 L stainless steel are built via directed energy deposition, with the tenth layer being subject to various peening processes (shot peening, hammer peening and laser shock peening). The microstructure of the eleventh layer of all the samples is then characterized to estimate the cooling rate. Findings: The measurements indicate that the application of interlayer peening causes a reduction in primary cellular arm spacing and an increase in micro segregation as compared to a sample prepared without interlayer peening. Both factors indicate an increase in the cooling rate brought about by the interlayer peening. Practical implications: This work provides insight into process design for hybrid AM processes as cooling rates are known to influence mechanical properties in laser-based AM. Originality/value: To the best of the authors’ knowledge, this work is the first of its kind to evaluate the effects of interlayer peening on a subsequently deposited layer in a hybrid AM process.